Learning from Friends: Developing appreciations for unknowing in reflexive practice. Issue 2 (April 2017) - Allen, Stephen
In this article, I develop a new perspective on being reflexive, which appreciates unknowing as a core aspect. The intention is to promote more inclusive and equitable ways of managing and organising. By drawing on my own and others' experiences of the 'business method' of the Religious Society of Friends, or Quakers, images of the possibilities for reflexive practice, which embrace individual unknowing and help foster systemic intelligence, are explored. A relational ontology is pursued as these ideas can offer a suitable bridge to bring the processes of Quakers into conversation with debates about reflexive practice. The implication is that in the perspective developed, managing reflexively can be understood as a collective practice of searching for unity, or 'sense of the meeting', which is achieved through relational processes.